The Well‐Ordered Society under Crisis: A Formal Analysis of Public Reason vs. Convergence Discourse. Issue 1 (5th July 2019) - Chung, Hun
Abstract: A well‐ordered society faces a crisis whenever a sufficient number of noncompliers enter into the political system. This has the potential to destabilize liberal democratic political order. This article provides a formal analysis of two competing solutions to the problem of political stability offered in the public reason liberalism literature—namely, using public reason or using convergence discourse to restore liberal democratic political order in the well‐ordered society. The formal analyses offered in this article show that using public reason fails completely, and using convergent discourse, although doing better, has its own critical limitations that have not been previously recognized properly.